2022
DOI: 10.1159/000526956
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Adherence to Recommended Physical Activity and Its Association with Mortality and Disease Progression among US Adults with Chronic Kidney Disease

Abstract: <b><i>Introduction:</i></b> This study aimed to examine the trends in adherence to the Physical Activity Guidelines (PAG) for aerobic activity and sedentary time and their effects on mortality and disease progression among US adults with chronic kidney disease (CKD). <b><i>Methods:</i></b> We studied individuals from the National Health and Nutrition Examination Survey 2007–08 to 2017–18 with a mortality file in 2015. Multivariate regression models were used to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In another study, the top priority for older CKD patients was maintaining independence through physical activity, whereas for younger patients, longevity and transplant candidacy were the most important motivating factors [ 38 ]. Evidence from cohort studies suggests that adherence to physical activity guidelines is significantly associated with all-cause mortality (HR: 0.49; 95% CI: 0.38–0.63), malignancy mortality (HR: 0.30; 95% CI: 0.17–0.52), and albumin-to-creatinine ratio (OR: -0.27; 95% CI: -0.39 to -0.15) [ 39 ]. A retrospective study showed that ‘non-completers’ (successful completion of a pragmatic renal rehabilitation program more than 50%) of renal rehabilitation had a 1.6-fold (95% CI 1.00-2.58) greater risk of a combined event [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, the top priority for older CKD patients was maintaining independence through physical activity, whereas for younger patients, longevity and transplant candidacy were the most important motivating factors [ 38 ]. Evidence from cohort studies suggests that adherence to physical activity guidelines is significantly associated with all-cause mortality (HR: 0.49; 95% CI: 0.38–0.63), malignancy mortality (HR: 0.30; 95% CI: 0.17–0.52), and albumin-to-creatinine ratio (OR: -0.27; 95% CI: -0.39 to -0.15) [ 39 ]. A retrospective study showed that ‘non-completers’ (successful completion of a pragmatic renal rehabilitation program more than 50%) of renal rehabilitation had a 1.6-fold (95% CI 1.00-2.58) greater risk of a combined event [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…23 In addition, among nondialysis patients with CKD, extended sedentary time was associated with risk of all-cause and CVD-related mortality. 24 , 25 These studies reported a linear association between sedentary time and mortality risk, which was questionable. A systematic review demonstrated a nonlinear association between total sitting time and all-cause mortality in general population, with a threshold identified at 3–4 hours per day of TV viewing, above which the risk was significantly increased.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study examined the association between adherence to physical activity guidelines for aerobic activity and sedentary time, and their effects on mortality and disease progression among US adults with CKD. It found that increased aerobic activity and reduced sedentary time were associated with decreased mortality and prevention of disease progression (8). Additionally, resistance exercise training has been shown to increase muscle size and strength.…”
Section: Introductionmentioning
confidence: 99%